2021
DOI: 10.3390/ijms22126586
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Zone Steroids and Estrogen Show Sex Specific Effects on Oligodendrocyte Precursor Cells in Response to Oxidative Damage

Abstract: Oxygen causes white matter damage in preterm infants and male sex is a major risk factor for poor neurological outcome, which speculates the role of steroid hormones in sex-based differences. Preterm birth is accompanied by a drop in 17β-estradiol (E2) and progesterone along with increased levels of fetal zone steroids (FZS). We performed a sex-based analysis on the FZS concentration differences in urine samples collected from preterm and term infants. We show that, in preterm urine samples, the total concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…These studies, however, did not consider the continuing postnatal synthesis of fetal zone steroids by the adrenal of the preterm infant. Our current and previous findings [ 7 , 19 ] have elaborated the neuroprotective effects of FZS and either no or even harmful effects when FZS are combined with estradiol. Therefore, here, we add new insights to clarify the question whether maintaining the placental hormone level after preterm birth is a promising therapeutic strategy, and our approach considers the unique hormonal milieu of the preterm infant with high postnatal production of FZS.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…These studies, however, did not consider the continuing postnatal synthesis of fetal zone steroids by the adrenal of the preterm infant. Our current and previous findings [ 7 , 19 ] have elaborated the neuroprotective effects of FZS and either no or even harmful effects when FZS are combined with estradiol. Therefore, here, we add new insights to clarify the question whether maintaining the placental hormone level after preterm birth is a promising therapeutic strategy, and our approach considers the unique hormonal milieu of the preterm infant with high postnatal production of FZS.…”
Section: Discussionsupporting
confidence: 59%
“…Placenta is the main source of estrogen during pregnancy [ 6 ], and the fetus provides 90% of the androgenic precursors required for the synthesis of estrogen. The active steroidogenic specialized compartment of the fetal adrenal cortex is called the fetal zone, which together with the placenta forms an effective steroid exchange channel, and this functional association is termed as the “fetoplacental unit” [ 7 ]. The fetus is constantly exposed to the changing hormone levels during its crucial stages of development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the study of BPD with brain injury, the period of hyperoxic exposure can be up to 14 days ( Table 1 ). Sex differences in adverse neurological outcomes have been identified in clinical studies and experimentally [ [15] , [16] , [17] , [18] , [19] ], with females having a superior prognosis to males [ 20 ]. A study by Donna et al showed that stronger regulation of estrogen receptor alpha in female cells allowed them to better cope with oxidative stress [ 19 ].…”
Section: Experimental Modelsmentioning
confidence: 99%